Prognostic value of early reduction of BCR/ABL1 gene expression in criteria of deep molecular response on imatynib therapy in patients with chronic myeloid leukemia - Дмитренко, І. В. (Problems of Environmental Biotechnology, 2018)
Achieving a deep molecular response (MR4) is a prerequisite for imatinib therapy discontinuation in patients with chronic myeloid leukemia (CML). 313 patients with a chronic phase of CML at the age from 18 to 80 years (Me = 42 years) were examined to determine the range of informative early criteria that will allow to select patients with a high probability of MR4 by 24 months of imatinib therapy. The prediction value of the BCR/ABL1 transcript level at 3 months and 6 months of imatinib therapy and initial clinical-laboratory and demographic factors were analyzed (age, sex, risk group for Sokal, Hasford, EUTOS and ELTS systems, duration of therapy before imatinib and BCR/ABL1 transcript type). By multivariate analysis, the type of BCR/ABL1 transcript (p = 0.045) and the duration of therapy before imatinib (p = 0.006) were the initial independent predictors of a deep molecular response at 24 months. The BCR/ABL1 transcript level at 3 months and 6 months were also significantly associated with the reduction of the tumor clone to the level of MR4 at 24 months of therapy. The threshold ​​for the BCR/ABL1 transcript level was determined to be 3.7 % at 3 months and BCR/ABL1 = 0.4 % at 6 months. The excess of these threshold increased the risk of deep molecular response failure at 24 months. It is shown that the inclusion the BCR/ABL1 < 3.7 % at 3 months as an additional factor significantly increased the accuracy of prognosis the MR4 at 24 months and eliminated the importance of other prognostic factors.